Pre- and during- labour predictors of dystocia in active phase of labour: a case-control study - Jila Nahaee; Fatemeh Abbas-Alizadeh; Mojgan Mirghafourvand; Sakineh Mohammad-Al (BMC, 2020)
Abstract Background Labour dystocia (LD) is associated with maternal and foeto-neonatal complications and increased rate of caesarean section. There are scant studies on predictive factors of labour dystocia in Iran, as well as in other countries. Therefore, this study aimed to identify the predictive factors of LD using an integrated and collaborative pre- and during- labour factors to help formulate more effective intervention strategies for prevention and management of LD. Methods In this case-control study, 350 women with and 350 women without LD, matched individually in terms of parity and hospital, were compared. The participants were in active labor, had singleton pregnancy, live foetus with a cephalic presentation, gestational age of 37+ 0-41+ 6 weeks, and were hospitalized for vaginal birth in two teaching hospitals in Tabriz, Iran. Data related to the socio-demographic characteristics, anxiety status (using the Spielberger State Anxiety Inventory), and woman dehydration were collected at cervical dilatation between 4 and 6 cm (before dystocia detection) and the other data at different phases of labour, and after birth (before discharge). The multivariate logistic regression was used to determine the predictors. Results The predictors of LD were severe [OR 58.0 (95% CI 26.9 to 125.1)] and moderate [8.6 (4.2 to 17.4)] anxiety, woman dehydration > 3 h [18.67 (4.0 to 87.3)] and ≤ 3 h [2.8 (1.7 to 4.8], insufficient support by the medical staff in the delivery room [5.8 (1.9 to 17.9)], remifentanil administration [3.1 (1.5 to 6.2)], labour induction [4.2 (2.5 to 7.2], low income [2.0 (1.2 to 3.3)], woman's height < 160 cm [2.0 (1.1 to 3.3)], and woman age of 16-20 y [0.3 (0.2 to 0.6)]. The proportion of the variance explained by all these factors was 74%. Conclusion The controllable predictors, such as woman anxiety and dehydration, and insufficient support from medical staff during labour were strongly associated with the risk of LD. Therefore, it seems that responding to woman physical, psychological, and supportive needs during labour can play a significant role in LD prevention and control. Ethical code IR.TBZMED.REC.1397.624.